2008
DOI: 10.1074/jbc.m709698200
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin Contributes to the Acquired Apoptotic Resistance of Human Mesothelioma Multicellular Spheroids

Abstract: When grown as three-dimensional structures, tumor cells can acquire an additional multicellular resistance to apoptosis that may mimic the chemoresistance found in solid tumors. We developed a multicellular spheroid model of malignant mesothelioma to investigate molecular mechanisms of acquired apoptotic resistance. We found that mesothelioma cell lines, when grown as multicellular spheroids, acquired resistance to a variety of apoptotic stimuli, including combinations of tumor necrosis factor-related apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
124
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(132 citation statements)
references
References 63 publications
(75 reference statements)
8
124
0
Order By: Relevance
“…Nevertheless, phospho-Akt has previously been described as being downregulated in MPM cells cultured under NA conditions without the occurrence of apoptosis. 29,30 In this study, we found that the ERK pathway was also rapidly downregulated in NA MPM cells. By contrast, downregulation of phospho-Akt and phospho-ERK in non-tumoral MeT-5A was associated with anoikis.…”
Section: Discussionmentioning
confidence: 61%
“…Nevertheless, phospho-Akt has previously been described as being downregulated in MPM cells cultured under NA conditions without the occurrence of apoptosis. 29,30 In this study, we found that the ERK pathway was also rapidly downregulated in NA MPM cells. By contrast, downregulation of phospho-Akt and phospho-ERK in non-tumoral MeT-5A was associated with anoikis.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, in 3D models, cells seem to express distinct genes usually associated with drug resistance that were also found in in vivo animal studies (58). Factors, such as alteration of chromatin structure, apoptosis inhibition, cell cycle and permeability, make the MCTS a more reliable and predictable drug testing in vitro model compared to 2D monolayer models (29,37,(62)(63)(64). Radiation resistance has also been linked to spheroid models in the past.…”
Section: Anticancer Researchmentioning
confidence: 99%
“…The acquired MCR has been demonstrated to be linked to a limitation of drug diffusion, to the activation of survival pathways such as NF-κB or mTOR, or to the upregulation of p27 (5)(6)(7)(8)(9). However, the molecular basis of MCR is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…However, the 2D monolayer in vitro model does not exhibit the full range of drug resistance observed in in vivo solid tumours. For this reason, three-dimensional (3D) multicellular tumour spheroids (MTS) have been used as an in vitro model of solid tumours for drug resistance studies because they mimic the growth characteristics of in vivo tumours more closely than cancer cell line monolayers (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%